Analysing strategic environmental assessment towards better decision-making - Caratti, Pietro, 1972-; Dalkmann, Holger, 1970-; Jiliberto H., Rodrigo; Edward Elgar Publishing (Cheltenham, U.K. ; Northhampton, Mass. : Edward Elgar, 2004)
Analytical Strategic Environmental Assessment (ANSEA) is an insightful new approach to environmental evaluation, based on decision theory, policy analysis and environmental considerations. These concepts, though not new in their own fields of application, are combined and integrated in an innovative fashion. This book presents recent research on the implementation of the ANSEA approach which aims to ensure environmental values are properly integrated into the decision-making process.
pt. 1. ANSEA theoretical background -- pt. 2. The ANSEA approach -- pt. 3. Illustrating the ANSEA approach in practice.
Includes bibliographical references and index.
Keywords: Environmental impact analysis; Strategic planning -- Environmental aspects; Electronic books